Under Pressure From Progressives, US Declassifies Documents Related to Chile Coup - Johnson, Jake (Common Dreams, 2023)
"Huge congratulations to the U.S. members who made this call from the delegation, and to all those who have fought like hell to declassify these files and bring justice for the bloody crimes of September 1973."
Keywords: 2023-08 August; Chile; Declassification; Dictatorship; Pinochet